Construction and luminescence property of a highly ordered 2D self-assembled amphiphilic bidentate organoplatinum(ii) complex. Issue 33 (15th March 2016) - Xiang, Yunjie; Li, Wenjing; Fang, Yuxi; Zhang, Dengqing; Li, Xianying; Jin, Wusong
Abstract : A red luminescent film was constructed by self-assembly of1-Pt from methanol. The film on a substrate, exhibiting multi-stimuli responsiveness, was further obtained. Abstract : Rod-coil shaped amphiphilic bidentate dichloro(phenanthroline)platinum(ii ) complexes, 1-Pt and2-Pt, which possess different hydrophilic lateral chains on one side of an identical aromatic rod core, are synthesized.1-Pt first forms dimers then arranges into well-defined two-dimensional (2D) films consisting of highly ordered molecular arrays both from methanol and on substrate.2-Pt, as a building-block, yields micrometer-sized rigid 2D sheets without formation of an initial dimer. Red luminescence of the film is induced by self-assembly of nonemissive1-Pt molecules, whereas sheets based on nonemissive2-Pt gives weak yellow emission. These results indicate that the coil-rod ratio plays an important role in the structure and optical properties of these self-assemblies. Moreover, the film on the substrate at the macroscopic scale, exhibits multi-stimuli responsiveness, which predicts its application in smart chemosensing devices and probes.